2021
DOI: 10.1002/ejoc.202100756
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Synthesis of Anthranils by PhIO Mediated Heterocyclization of ortho‐Carbonyl Anilines

Abstract: Here, we report a metal‐free synthesis of anthranils from ortho‐carbonyl anilines using PhIO as a sole additive under ambient conditions. This methodology did not require any external additives and delivered anthranils in excellent yields with broad substrate scope. The mechanistic studies suggest that the reaction proceeds via in‐situ generation of iminoiodane leading to nitrene and a subsequent nucleophilic attack from oxygen of ortho‐carbonyl aniline on nitrene results in heterocyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The mechanistic investigation suggests the involvement of a nitrene intermediate giving the desired product with good functional group compatibility (Scheme 36). 95…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic investigation suggests the involvement of a nitrene intermediate giving the desired product with good functional group compatibility (Scheme 36). 95…”
Section: Synthesis and Functionalisation Of Heterocycles Using Hyperv...mentioning
confidence: 99%
“…The mechanistic investigation suggests the involvement of a nitrene intermediate giving the desired product with good functional group compatibility (Scheme 36). 95 As per the proposed mechanism, an intermediate (A) is generated via the interaction of a Lewis base ( 59 The benzoxazin-2-one nucleus represents a unique class of lactone compounds that exhibits outstanding biological and pharmacological activities. 96 In this regard, Chen et al reported the synthesis of benzoxazin-2-ones ( 62) via oxidative C-H annulation reaction of arylamines ( 61) with α-keto acids.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…2,1-Benzisoxazoles 1 were prepared according to the literature procedure . Other substrates and reagents were commercial and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…2,1-Benzisoxazoles and related N-heterocyclic compounds (also known as anthranils) are important starting materials for the synthesis of pharmaceutical intermediates, organic functional materials, and industrial surfactants. [1][2][3][4][5][6] For instance, anthranil derivatives are applied to treat several central nervous system abnormalities, 7,8 act as anti-inflammatory drugs, 9,10 and can be used to produce antiplatelet inhibitors, quinolinones, and acridone. [11][12][13][14] Due to fundamental significance and practical values of these compounds, several protocols have been developed for their synthesis.…”
Section: Introductionmentioning
confidence: 99%